Socio-Cultural Aspects of the Risk of Diabetes Mellitus in Tolotang Traditional Chairman (UWA) in Sidrap District - Mulfi Jumliah Agustin; Usman Usman; Fitriani Umar (Indonesian Health Journal, 2022)
Diabetes Mellitus cases are high in South Sulawesi, especially in Sidrap Regency, reaching (2.7%) while the national prevalence rate is (2.1%). The Tolotang culture respects traditional leaders by serving sweet foods, so there is a risk of Diabetes Mellitus. This study was to identify socio-cultural and dietary patterns to the risk of Diabetes Mellitus in Tolotang traditional leaders. This type of research is a mixed method. Informants in this study were traditional leaders and the Tolotang community in Sidrap Regency. Sampling was done by snowball sampling method. The results obtained are related to socio-culture; people often serve heavy foods high in calories and carbohydrates accompanied by snacks such as cakes and sweet drinks. The presentation of food for traditional leaders when tradition is done and specially prepared on a tray (large round tray made of iron) containing rice and side dishes, then using the board (a typical Bugis Makassar container used to serve cakes) filled with various types of cake snacks. It is different from people who do as usual by taking their food, which has been prepared during the ritual. The results showed that (60.0%) of traditional leaders had diabetes based on their current blood sugar levels. The traditional leader's calorie consumption (35.0%) is more, and (50.0%) is sufficient. Carbohydrate consumption (35.0%) is more, and (55.0%) is adequate. It was concluded that the traditional leader's diet was, on average, high in calories which contained many sources of carbohydrates and fats. It is suggested that there is a need for education to educate the public to serve healthier foods that are low in calories and fibre, such as vegetables and fruits